Fabrication of high-entropy REBa2Cu3O7−δ thin films by pulsed laser deposition. (1st May 2022) - Yamashita, Aichi; Hashimoto, Kazuki; Suzuki, Shunta; Nakanishi, Yusuke; Miyata, Yasumitsu; Maeda, Toshihiko; Mizuguchi, Yoshikazu
Abstract: Thin films of RE Ba2 Cu3 O7− δ ( RE 123, RE : rare earth) having a high-entropy (HE) RE site were successfully fabricated by the pulsed laser deposition method. Solution various RE elements result in increasing configurational entropy of mixing. Critical current density of the HE films exceeds an order of 1.0 MA cm −2 under conditions of T < 20 K and μ 0 H < 7 T. Since the HE effects have a potential to an improvement of irradiation tolerance, the present results encourage further development of HE RE 123 superconducting materials used in the environment with high magnetic fields and irradiation, for example in fusion reactors.